Africa 2050: Jobs and Prosperity in a Multipolar Global Economy— Moving Out of Fragility and Conflict. (May 2013) - Michailof, Serge
Most African states are unfortunately prone to some level of "inherent" fragility, influenced by the level of government inclusiveness and legitimacy and the quality of the state's main institutions. Inclusive political systems and/or a well-functioning democracy may lower inherent fragility. But democracy and political inclusiveness are no guarantee of state resilience; basic economic reforms and strong growth are not incompatible with state fragility. The deeply ingrained social and historical character of inherent fragility explains why moving out of fragility is so difficult. Institution-building during times of crisis—specific tensions, stresses, and shocks—is usually necessary to transition from fragility to resilience.